2015
DOI: 10.17058/reci.v4i4.4777
|View full text |Cite
|
Sign up to set email alerts
|

A Influência Da Incontinência Urinária Na Satisfação Sexual E Na Qualidade De Vida Em Mulheres Climatéricas

Abstract: Justificativa e Objetivos:A perda da continência urinária pode afetar até 50% das mulheres em alguma fase de suas vidas e cerca de 60% das mulheres acima dos 60 e esta pode influenciar na satisfação sexual. O objetivo deste estudo foi avaliar qual a influência da incontinência urinária na satisfação sexual e perante a qualidade de vida em mulheres climatéricas. Métodos: A amostra foi composta por 28 mulheres no período climatérico com idade entre 43 a 70 anos de idade. As voluntárias foram submetidas a três qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…A study by Frigo et al [18] found that UI can occur due to functional changes that may have an organic or psychosocial cause, possibly leading to development of SD, i.e., a total or partial blockage of the normal sexual response. Satisfaction in this aspect may be affected not only by the presence of physiological changes but also by the emotional consequences, loss of self-esteem, shame and feelings of social inadequacy.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Frigo et al [18] found that UI can occur due to functional changes that may have an organic or psychosocial cause, possibly leading to development of SD, i.e., a total or partial blockage of the normal sexual response. Satisfaction in this aspect may be affected not only by the presence of physiological changes but also by the emotional consequences, loss of self-esteem, shame and feelings of social inadequacy.…”
Section: Discussionmentioning
confidence: 99%
“…The seventh question requires a different treatment, that is, the score of the given answer (0-5) must be subtracted from 5 to have the final score of that question. The highest scores indicate a better pattern of sexual activity/satisfaction, according to the following breakdown: good to excellent (82-100); above moderate to good (62-80); moderate to above moderate (42-60); poor to moderate (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); null to poor (0-20), null meaning no sexual activity. Data related to sociodemographic variables, clinical characteristics, climacteric symptomatology and sexuality characteristics were extracted from the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…This result can be explained by Ribeiro and Raimundo 28 who found that women adjust to the situation over time and gain confidence to have pleasant sexual intercourses. Frigo et al 29 found that the "moderate to above moderate" category had the highest prevalence rate, while the "null to poor" category had the lowest. Once again, this climacteric symptom could not be proved in this study.…”
Section: Sociodemographic and Hypoestrogenism Characteristicsmentioning
confidence: 99%